Saving working-time as the essence of the fetishism of computer science - Santos Neto, Artur Bispo dos (Argumentum, 2022)
This essay analyses the modern fetishism of computer science, in which the mystification emanating from the universe of commodity reaches its highest form. The fetishism analysed by Karl Marx in Capital serves as an inflection point for the interpretation of computer science. The analyses carried out by Prado and Teixeira forms basic presuppositions for the understanding of the vicissitudes of fetishism that shape contemporary scientific-technological knowledge. Finally, through the mediation of the considerations of István Mészáros, we highlight how the scientific-technological knowledge imposed by the reproduction of capital needs to be completely replaced by a form of organization of production centered on associated work and no longer on abstract work.